2020
DOI: 10.1002/jdd.12141
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary evaluation of dental hygiene curriculum: Assessment and management of peri‐implant conditions and diseases

Abstract: Objective: The purpose of this study was to investigate dental hygiene (DH) educational programs' didactic and clinical curriculum in the management of peri-implant diseases and conditions. The specific aims were (1) assess if evidence-based content for peri-implant diseases and conditions are currently included in didactic and clinical DH curriculum and (2) determine if DH education programs are currently preparing students at a level of clinical competency for the assessment and management of periimplant dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 35 publications
2
0
0
Order By: Relevance
“…Nearly all program directors (99%) were familiar with the revisions made in the new 2017 staging and grading system, which is an increase from the Arnett's 2020 national study, which reported 93% of DH faculty members were aware of the new AAP and EFP classification scheme of periodontal and peri-implant diseases and conditions. 7 Thus, this study can confirm an increase in the new AAP and EFP periodontal classification system awareness in the US. Moreover, this study revealed that most DH programs (91%) had already implemented the new staging and grading system into their curricula, which is likely due to the integration of the new staging and grading system into the NBDHE.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Nearly all program directors (99%) were familiar with the revisions made in the new 2017 staging and grading system, which is an increase from the Arnett's 2020 national study, which reported 93% of DH faculty members were aware of the new AAP and EFP classification scheme of periodontal and peri-implant diseases and conditions. 7 Thus, this study can confirm an increase in the new AAP and EFP periodontal classification system awareness in the US. Moreover, this study revealed that most DH programs (91%) had already implemented the new staging and grading system into their curricula, which is likely due to the integration of the new staging and grading system into the NBDHE.…”
Section: Discussionsupporting
confidence: 63%
“…While this study was an international study, 97% of respondents were US‐based DH education program directors. Nearly all program directors (99%) were familiar with the revisions made in the new 2017 staging and grading system, which is an increase from the Arnett's 2020 national study, which reported 93% of DH faculty members were aware of the new AAP and EFP classification scheme of periodontal and peri‐implant diseases and conditions 7 . Thus, this study can confirm an increase in the new AAP and EFP periodontal classification system awareness in the US.…”
Section: Discussionsupporting
confidence: 50%